171k views
17 votes
Answer to letter B , C, D

Answer to letter B , C, D-example-1

1 Answer

8 votes

Answer:

  • See below.

Explanation:

Our expression given: 3(x-6) + 2y

A. Substitute x = -7 and y = 10 into the equation.


3( - 7 - 6) + 2(10)

Use the Distributive Property:


- 21 - 18 + 20

Solve:


- 19

B. Substitute x = 5 and y = -2 into the equation.


3(5 - 6) + 2( - 2)

Use the Distributive Property:


15 - 18 + -4

Solve:


-7

C. Substitute x = 0 and y = 6 into the equation.


3(0 - 6) + 2(6)

Use the Distributive Property:


- 18 + 12

Solve:


-6

D. Substitute x = 3 and y = 3 into the equation.


3(3 - 6) + 2(3)

Use the Distributive Property:


9 - 18 + 6

Solve:


-3

User Kevin Hussey
by
5.0k points